LEISHMANIOSIS DISEASE, ITS SYMPTOMS, PRIMARY CONSEQUENCES AND DISTRIBUTION - Ahmedova Saodat Tashboltayevna; Asfandiyorov Javodbek Mirzaali o‘g‘li; Odilov Ramziddin Dilshod o‘g‘li; Xushvaqtova Osiyo Asadulla qizi; Rashidova Farangiz Musulmon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides detailed information about leishmaniasis and its primary symptoms. Also, this article describes in detail the types, stages, and consequences of leishmaniasis, as well as the spread of this disease in the territory of Uzbekistan, in which regions it is widespread, and the ways of spreading leishmaniasis.